Development and student evaluation of an Internet-based Control Engineering Laboratory. Issue 29 (2015) - Chevalier, Amélie; Bura, Monica; Copot, Cosmin; Ionescu, Clara; Keyser, Robin De
Abstract: This paper presents the structure, functionality and application of an improved Remote Laboratory for engineering students hosted at Ghent University. The Remote Laboratory consists of two setups: Ball and Plate system and Quadruple Water Tank system. These setups introduce basic control aspects such as PID control design and non-minimum phase systems. Also more challenging aspects such as multiple-input-multiple-output control, decoupled and decentralized systems and advanced control strategies such as Internal Model Control or Model Predictive Control can be investigated on the setups. Based on a feedback study that targeted the bachelor degree students, the level of effectiveness of this concept has been shown but also possible functional enhancements that can be applied to the systems have been pointed out. The feedback survey data concluded that the Remote Laboratory has attracted the attention of students and had a positive impact in their training.